P-wave velocity of discrete samples (DPW) from IODP Hole 386-M0084E - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
P-wave velocity data from discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). During the onshore phase of expedition 386, which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu, discrete samples for P-wave velocity measurements were taken from the work halves approx. every 2 meter down core using syringes with an inner diameter of 2 cm. Samples measured 2.5–3 cm long for a sample volume of ~10 cubic centimetres. Samples were then shipped to the European Petrophysics Consortium (EPC) laboratory at the University of Leicester (UK) for processing. Measurements were performed with a Geotek P-wave logger for discrete samples (PWL-D). Measurements were attempted for each sample, however, the unconsolidated lithology of some samples proved unsuitable for the instrument (e.g. too soupy or too friable to be placed between the transducers). Operator notes: Data from section numbers > 30 can be associated to a decrease in velocity values, this is likely due to cracks opening in the samples when applying pressure on it at the time of measurement (as observed by operators). For holes M0081E & F Sections 1-29 velocity values are overestimated due to an issue with the calibration. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023